Hummingbirds - Bader, Bonnie, 1961- (Penguin core concepts., 2015)
"Hummingbirds are some of the most beautiful, tiniest birds in nature. They are the only creatures that can fly forward, backward, sideways--even upside down! Their hearts beat anywhere from 500 to 1200 times every minute; their wings flap as many as 80 times per second; and they breathe up to 600 times per minute. This fact-and-photo-filled nonfiction 8x8 will leave readers astounded by the smallest bird in America!"--